Immunomodulatory Therapy Does Not Increase the Risk of Cancer in Persons With Inflammatory Bowel Disease and a History of Extracolonic Cancers. (May 2019) - Mañosa, Míriam; Chaparro, M.; Juan, A.; Aràjol, C.; Alfaro, I.; Mínguez, M.; Velayos, B.; Benítez, J.M.; Mesonero, F.; Sicilia, B.; Zabana, Y.; Villoria, A.; et al.
Abstract : OBJECTIVES: Immunosuppressant therapies (IMTs; thiopurines, anti–tumor necrosis factor agents) may influence the immunologic control of cancer and might facilitate the spread and recurrence of cancer. This study assesses the impact of the use of IMTs on the development of incident cancers (recurrent or new) in patients with inflammatory bowel disease (IBD) and a history of malignancy. METHODS: Patients with IBD included in the ENEIDA registry with a history of cancer without being exposed to IMTs were identified and retrospectively reviewed and compared regarding further treatment with IMTs or not by means of a log-rank test. RESULTS: Overall, 520 patients with previous extracolonic cancer naive to IMTs before the diagnosis of cancer were identified. Of these, 146 were subsequently treated with IMTs ( exposed ), whereas 374 were not ( nonexposed ). The proportion of patients with incident cancers was similar in both exposed (16%) and nonexposed (18%) patients ( P = 0.53); however, there was more than a 10-year difference in the age at index cancer between these 2 groups. Cancer-free survival was 99%, 98%, and 97% at 1, 2, and 5 years in exposed patients, and 97%, 96%, and 92% at 1, 2, and 5 years in non-exposed patients, respectively ( P = 0.03). No differences in incident cancer rates were observed between exposed and nonexposed patients when including only those who were exposed within the first 5 years after cancer diagnosis. DISCUSSION: In patients with IBD and a history of cancer not related to immunosuppression, the use of IMTs is not associated with an increased risk of new or recurrent cancers even when IMTs are started early after cancer diagnosis.